Disparities in access to palliative care facilities for patients with and without cancer: A retrospective review. (June 2021) - Lau, Christine; Meaney, Christopher; Morgan, Matthew; Cook, Rose; Zimmermann, Camilla; Wentlandt, Kirsten
Background: To date, little is known about the characteristics of patients who are admitted to a palliative care bed for end-of-life care. Previous data suggest that there are disparities in access to palliative care services based on age, sex, diagnosis, and socioeconomic status, but it is unclear whether these differences impact access to a palliative care bed. Aim: To better identify patient factors associated with the likelihood/rate of admission to a palliative care bed. Design: A retrospective chart review of all initiated palliative care bed applications through an electronic referral program was conducted over a 24-month period. Setting/participants: Patients who apply and are admitted to a palliative care bed in a Canadian metropolitan city. Results: A total of 2743 patients made a total of 5202 bed applications to 9 hospice/palliative care units in 2015–2016. Referred and admitted cancer patients were younger, male, and more functional than compared to non-cancer patients (all p  < 0.001). Referred and admitted patients without cancer were more advanced in their illness trajectory, with an anticipated prognosis <1 month and Palliative Performance Status of 10%–20% (all p  < 0.001). On multivariate analysis, a diagnosis of cancer and a prognosis of <3 months were associated with increased likelihood and/or rate of admission to a bed, whereas the presence of care needs, a longer prognosis and a PPS of 30%–40% were associated with decreased rates and/or likelihood of admission. Conclusion: Patients without cancer have reduced access to palliative care facilities at end-of-life compared to patients with cancer; at the time of their application and admission, they are "sicker" with very low performance status and poorer prognoses. Further studies investigating disease-specific clinical variables and support requirements may provide more insights into these observed disparities.